Strategi Humas Pemerintah Kabupaten Sumedang Dalam Mensosialisasikan Layanan Digital ”Wa Kepo” - Maulida, Raisya Wahyuning; Nugraha, Aat Ruchiat (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In government administration, Public Relations has a strategic role and function to provide information services about government policies and work programs for the public. Communication strategies are needed to help people develop effective communication programs to achieve government goals, namely public participation in policy. Sumedang Regency Government Public Relations faces the challenge of socializing WA KEPO digital services to realize the Sumedang Happy Digital Region program. This research aims to determine the Sumedang Regency Government Public Relations communication strategy in socializing the WA KEPO digital platform service. This research uses a qualitative descriptive method with data obtained through interviews, observation, and literature study. The research results show that the Sumedang Regency Government Public Relations has used educational and persuasive strategies, cooperative strategies, as well as integrative and coordinating strategies in socializing WA KEPO digital services. However, optimization is needed in educational and persuasive strategies to provide understanding to the public about WA KEPO digital services.